Genome-wide association study of mitochondrial DNA in Chinese men identifies seven new susceptibility loci for high-altitude pulmonary oedema - Tang, Caizhi; Chen, Yu; Liu, Xinyuan; Ran, Zhuang; Luo, Yongjun (Vojnosanitetski pregled, 2022)
Background/Aim. High-altitude pulmonary oedema (HAPE), which normally occurs at altitudes higher than 3,000 m, is a potentially fatal disease due to hypoxia. The role of mitochondrial genomes in determining an individual's susceptibility to HAPE has not been determined yet. However, a number of genetic polymorphisms have recently been found to be overrepresented in HAPE patients. The majority of published genome-wide association studies have investigated only a small number of top-ranking single-nucleotide polymorphisms (SNPs)/genes by the overview of nuclear DNA and considered each of the identified SNPs/genes independently. Little research has been conducted on mitochondrial genomes in relapsing HAPE patients by genome-wide association studies. Methods. To identify biological pathways important to HAPE occurrence, we examined approximately 500,000 SNPs genome-wide from 10 unrelated cases of relapsing HAPE and we compared the SNPs in these cases with those in the Chinese in Beijing, China population (45 controls) to discover the association between genotypes and HAPE susceptibility among the mitochondrial function-related genes. We used the FUMA platform to expand those SNPs to selected candidate SNPs. Results. A total of 369 candidate SNPs, 4 lead SNPs, 4 genomic risk loci and 5 mapped genes were obtained. The 7 mapped genes were ADAMTS9-AS2, NEK1, CLCN3, C4orf27(HPF1), RP11-219J21.2, ANKRD26 and YME1L1. Conclusion. This study confirms the association of ADAMTS9-AS2, NEK1, CLCN3, C4orf27(HPF1), RP11-219J21.2, ANKRD26 and YME1L1 with HAPE, which may provide future targets for the treatment of this disease.
Keywords: genetic techniques; genome; hypoxia; polymorphism, genetic; pulmonary oedema; pulmonaty edema of mountaineers